Just What the Doctor Ordered: A Guide to Robust Assessment and Exercise Prescription in Older Adults. (November 2021) - Schlicht, Jeffrey A.; Inskip, Michael; Fiatarone Singh, Maria
Abstract : Apply It!: Screening for frailty, cognitive impairment, depression, malnutrition, inappropriate medications, and falls risk provides important information for your client's portfolio. Proper exercise modalities and progression are key to creating a safe and effective exercise prescription. High-intensity strength training is safe and should be prescribed to even the most frail older adults. Abstract : Summary Statement Learn techniques to assess your older clients' physical, mental, and emotional states and use that information to create a powerful Get Up, Stay Up, Move exercise prescription.